2020
DOI: 10.1136/esmoopen-2020-000679
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical validation study of 15-gene biomarker panel predictive of benefit from adjuvant chemotherapy in resected non-small-cell lung cancer: analysis of JBR.10

Abstract: ObjectiveThere are no validated approaches to predict benefit from adjuvant chemotherapy for resected patients with non-small-cell lung cancer (NSCLC). The aim of this study was to translate a 15-gene mRNA expression profile published by Zhu et al, shown to be prognostic and predictive of benefit, into a readily applicable immunohistochemistry (IHC) panel.MethodsFor seven of the genes in the gene expression profile (GEP) for which suitable commercial antibodies were available, we semiquantitatively assessed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Importantly, the TCGA data were not limited to LUAD but instead included all tumor types that received taxane treatment and reported outcomes, such that breast cancer was the majority tumor type. Taxanes are primarily used in the treatment of breast cancer, NSCLC, and prostate cancer, which together make up an estimated 30 to 40% of new cancer cases in the United States (48). Our findings raise the possibility that STMN2 levels might serve as a predictive biomarker for either taxane response or cotreatment with PRMT5i and taxanes, upon Food and Drug Administration approval, and certainly provide clear rationale for investigating STMN2's role in cancer.…”
Section: Discussionmentioning
confidence: 74%
“…Importantly, the TCGA data were not limited to LUAD but instead included all tumor types that received taxane treatment and reported outcomes, such that breast cancer was the majority tumor type. Taxanes are primarily used in the treatment of breast cancer, NSCLC, and prostate cancer, which together make up an estimated 30 to 40% of new cancer cases in the United States (48). Our findings raise the possibility that STMN2 levels might serve as a predictive biomarker for either taxane response or cotreatment with PRMT5i and taxanes, upon Food and Drug Administration approval, and certainly provide clear rationale for investigating STMN2's role in cancer.…”
Section: Discussionmentioning
confidence: 74%
“…For example, Zhu et al reported the identification of prognostic or predictive gene expression signatures for NSCLC by microarray analysis of specimens collected prospectively from a randomized phase III adjuvant chemotherapy trial [18]. However, significant reproducibility in subsequent validation studies was not achieved for this predictive signature [21]. Because various factors are involved in the therapeutic effect of cytotoxic anticancer agents, it may be difficult to predict a clear-cut therapeutic effect using only a single biomarker or biomarkers that do not consider the interrelationships between genes.…”
Section: Introductionmentioning
confidence: 99%